Pacem in Terris: Are Papal Visits Good News for Human Rights? - Marek Endrich; Jerg Gutmann (University of Hamburg, Institute of Law and Economics (ILE), 2020)
We analyze the effect of state visits by the Catholic pope on human rights in the host country to illustrate how a small theocracy like the Vatican can exert significant political influence in international politics. Our theoretical model of the strategic interaction between the Catholic Church and the government shows how the pope uses the threat of shaming to incentivize governments to refrain from violations of human rights. Drawing on a new dataset of papal state visits outside Italy and a novel identification strategy, we test the hypothesis that governments react in anticipation of a papal visit by improving human rights protection. The existence of such a causal effect is supported by the data.
Keywords: D74; D78; F5; K38; P16; P26; P48; Z12; 300; Catholic Church; human rights; political economy; pope; repression; shaming